ASP8273 tolerability and antitumor activity in tyrosine kinase inhibitor‐naïve Japanese patients with EGFR mutation‐positive non‐small‐cell lung cancer. Issue 8 (29th June 2018) - Azuma, Koichi; Nishio, Makoto; Hayashi, Hidetoshi; Kiura, Katsuyuki; Satouchi, Miyako; Sugawara, Shunichi; Hida, Toyoaki; Iwamoto, Yasuo; Inoue, Akira; Takeda, Koji; Ikeda, Satoshi; Nakagawa, Tomoki; et al.
Abstract : Epidermal growth factor receptor ( EGFR ) activating mutations occur in approximately 50% of East Asian patients with non‐small‐cell lung cancer (NSCLC) and confer sensitivity to tyrosine kinase inhibitors (TKIs). ASP8273 is an irreversible EGFR‐TKI, given orally, that inhibits EGFR activating mutations and has shown clinical activity in patients with EGFR mutation‐positive NSCLC. Epidermal growth factor receptor‐TKI‐naïve Japanese adult patients (≥20 years) with NSCLC harboring EGFR mutations were enrolled in this open‐label, single‐arm, phase II study (ClinicalTrials.gov identifier NCT02500927). Patients received ASP8273 300 mg once daily until discontinuation criteria were met. The primary end‐point was to determine the safety of ASP8273 300 mg; the secondary end‐point was antitumor activity defined by RECIST version 1.1. Thirty‐one patients (12 men and 19 women; median age, 64 years [range, 31‐82 years]) with EGFR mutation‐positive NSCLC were enrolled; as of 23 February 2016, 25 patients (81%) were still on study. Of the 31 patients, 27 (87%) had an exon 19 deletion (n = 13, 42%) or an L858R (n = 14, 45%) EGFR activating mutation, and two (7%) had an L861Q mutation. Five patients (16%) had other EGFR activating mutations, two had an activating mutation and the T790M resistance mutation. The most commonly reported treatment‐emergent adverse event was diarrhea (n = 24, 77%). All patients had at least one post‐baseline scan; one patient (3%) achieved a confirmed complete response, 13 (42%) had a confirmed partial response, and 15 (48%) had confirmed stable disease (disease control rate, 94% [n = 29/31]) per investigator assessment. Once‐daily ASP8273 at 300 mg was generally well tolerated and showed antitumor activity in TKI‐naïve Japanese patients with EGFR mutation‐positive NSCLC. Abstract : This open‐label, single‐arm, phase II study (NCT02500927) assessed the safety and antitumor activity of ASP8273 in epidermal growth factor receptor–tyrosine kinase inhibitor (EGFR‐TKI)‐naïve Japanese adult patients with non‐small‐cell lung carcinoma (NSCLC) harboring EGFR mutations. ASP8273 is an orally administered, irreversible EGFR‐TKI that inhibits EGFR activating mutations and has shown clinical activity in patients with EGFR mutation‐positive NSCLC. Once‐daily ASP8273 at 300 mg was generally well tolerated and showed antitumor activity in TKI‐naïve Japanese patients with EGFR mutation‐positive NSCLC.